1977
DOI: 10.1163/002829678x00224
|View full text |Cite
|
Sign up to set email alerts
|

The Epithelium of the Gut as a Barrier Against Encapsulation By Blood Cells in Three Species of Parasitoids of Bupalus Piniarius (Lep., Geometridae)

Abstract: Three habitual parasites of the pine looper are generally not eliminated by the haemocytic defence reaction of their usual host, because the eggs are laid or the larvae settle behind the epithelium of the gut. This acts as a barrier against the passage of blood cells. This conclusion is supported by the observation that larvae of all three species are encapsulated during abnormally long stays in the host's body cavity. In two species this results from the parasitoid's failure to oviposit in the usual way, bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A third method of avoidance, applicable to endoparasitoids, is the placement of the egg by the parasitoid in select tissues where the egg hatches to develop out of reach of the immunocompetent hemolymph system [114,115]. For example, Klomp and Teerink [116] reported that two parasitoid diptera and one ichneumonid, all parasitic on the pine looper Bupulus piniurius, develop between the cuticular intima or peritrophic membrane and the epithelium of the digestive system, thus avoiding the immune system. Another example, provided by Silvestri [117], is where the eggs of Plufygustes dryomyiue deposited in host ganglia develop, but are rapidly encapsulated when placed in the host body cavity.…”
Section: Subversionmentioning
confidence: 99%
“…A third method of avoidance, applicable to endoparasitoids, is the placement of the egg by the parasitoid in select tissues where the egg hatches to develop out of reach of the immunocompetent hemolymph system [114,115]. For example, Klomp and Teerink [116] reported that two parasitoid diptera and one ichneumonid, all parasitic on the pine looper Bupulus piniurius, develop between the cuticular intima or peritrophic membrane and the epithelium of the digestive system, thus avoiding the immune system. Another example, provided by Silvestri [117], is where the eggs of Plufygustes dryomyiue deposited in host ganglia develop, but are rapidly encapsulated when placed in the host body cavity.…”
Section: Subversionmentioning
confidence: 99%
“…These usually have a single generation per year. A number of other species overwinter as first instar larvae in the fatty tissue of the host pupae (Klomp & Teerink, 1978). These are often bivoltine and many require a different host species in the spring and autumnal generations ( van Veen, 1981) whilst some species may even have two generations in a single host generation.…”
Section: Biologymentioning
confidence: 99%